Making a living professional musicians in live performances in Metro Manila - Dizon, Patricia Marie U.
"This study explores the identity of professional musicians. Using the ethnographic approach, this paper will investigate this identity through participant observation. Apart from critiquing the musicians' technical aspects of their performances, the study will offer an interpretation of the rationale behind the formulation of their repertoire in various contexts of use. Thus, the study incorporates the performance styles that are suitable for their respective audiences. In addition, this thesis will investigate the music production process, which will discuss how the musicians were chosen to perform for their respective audiences in varying settings, as well as how producers assign the repertoire to the performers."